The Effectiveness of Management of the Balong Dalem Tourist Attraction in Gunung Ciremai National Park (TNGC) - Shella Nur'azizah; N Nursahidin (Apollo: Journal of Tourism and Business, 2026)
The purpose of this research is to analyze the effectiveness of the management at the Balong Dalem tourism area in Gunung Ciremai National Park, Kuningan District. The management of a natural tourism area located in a conservation area finds it challenging to maintain a balance between economic, social, and environmental aspects. This research uses a qualitative descriptive approach and applies some data collection techniques like observation, in-depth interview, and documentation. The participants of the research were the PDAU leadership, Balai TNGC, and the residents in the area. The success criteria for this research can be measured using Duncan's model, which consists of goal accomplishment, integration, and adaptation. From the research results, we can say that the management at the Balong Dalem tourism area is very effective. Even though the organization has limited staff and an unstable leadership, there is always the setting of goals each year and five years ahead. There is integration amongst all participants in the project, although it has not yet been achieved. There have been changes brought about by the use of digital media, Some of the advantages include commitment to conservation, careful planning, and community participation. The lack of manpower, strict regulations, and lack of leadership continuity are some of the difficulties encountered.